Endoscopic Distal Iliotibial Band Z-Plasty for Greater Trochanteric Pain Syndrome - Peter Joachim Bruun Thomassen, M.D.; Jon Olav Drogset, M.D., Ph.D.; Olav Foss, M.D., Ph.D. (Arthroscopy Techniques)
Greater trochanteric pain syndrome (GTPS) includes idiopathic trochanteric pain, gluteus medius/minimus tendinopathy, and external snapping hip. If conservative treatment is unsuccessful, various open surgical procedures of the iliotibial band (ITB) at the level of the greater trochanter are available. Over the past few decades, endoscopic management of ITB and bursectomy for GTPS have been established as an alternative to open procedures. Better results and fewer complications are potential advantages of an endoscopic procedure. If surgery at the level of the greater trochanter fails, Z-plasty of the ITB at the level of the distal part of the femur may be considered. This operation relieves the ITB above the greater trochanter without exposing this area to further trauma. Traditionally, Z-plasty has been performed as an open procedure. This technical note describes an endoscopic method for the distal ITB Z-plasty.